Staged Concept for Treatment of Severe Postsaphenectomy Wound Infection - Thomas Schroeter; Sreekumar Subramanian; Michael A. Borger; Friedrich W. Mohr (Case Reports in Medicine)
The saphenous vein remains the most commonly used conduit in coronary artery bypass surgery. Vein harvest is a critical component with significant morbidity associated with leg wounds from open technique. Occurring complications are hematoma, postoperative pain, skin changes, neuropathy, and septic or nonseptic wound complications. Within the context of a recent case, we present our approach to postsaphenectomy wound management.